2009
DOI: 10.1118/1.3147144
|View full text |Cite
|
Sign up to set email alerts
|

Mapping structural changes in breast tissue disease using x‐ray scattering

Abstract: Spread of invasive carcinoma throughout breast tissue is believed to occur at supramolecular levels, beyond the range of standard histopathology identification. Small angle x-ray scattering (SAXS) is capable of characterizing the structural properties of collagen and tissue found in the breast at the scale of tens to hundreds of nanometers. Fifty-six patients who were treated with wide-local excision or mastectomy had tissue biopsy samples analyzed at 2 cm intervals along two perpendicular axes over their exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Also, the quantitative evaluation of forward-to-backward second harmonic generation signals have proven useful to differentiate invasive breast cancer and to monitor the progress of collagen changes during breast carcinogenesis [41]. It is worth mentioning that also another technique suited for analysis of large-scale organization of macromolecules, such as small angle x-ray scattering, was successfully employed to the identification of the structural aspects of collagen in breast cancer tissues, allowing discriminating regions of cancer cell invasion and predicting the direction of cancer spreading [42].…”
Section: Ex Vivo Studies On Collagen Composition and Architecture In mentioning
confidence: 99%
“…Also, the quantitative evaluation of forward-to-backward second harmonic generation signals have proven useful to differentiate invasive breast cancer and to monitor the progress of collagen changes during breast carcinogenesis [41]. It is worth mentioning that also another technique suited for analysis of large-scale organization of macromolecules, such as small angle x-ray scattering, was successfully employed to the identification of the structural aspects of collagen in breast cancer tissues, allowing discriminating regions of cancer cell invasion and predicting the direction of cancer spreading [42].…”
Section: Ex Vivo Studies On Collagen Composition and Architecture In mentioning
confidence: 99%
“…The structural information in ECM can differentiate invasive carcinoma from benign lesions or healthy tissue. Notably, the scatter profiles can even differentiate between normal tissues with and without a cancer history, which are not detectable by conventional morphological markers (Sidhu et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies, based both on the SAXS (Lewis et al, 2000;Fernandez et al, 2002;Round et al, 2005;Suhonen et al, 2005;Sidhu et al, 2009) and on the XRD modality (Kidane et al, 1999;Poletti et al, 2002;LeClair et al, 2006;Ryan and Farquharson, 2007;Oliveira et al, 2008), have shown the feasibility of breast tissue characterization. Of particular interest is the possibility of discriminating healthy and neoplastic tissue.…”
Section: Introductionmentioning
confidence: 99%